A Succession of MRI Scans Supports the Diagnosis of Lumbar Ligamentum Flavum Hematoma: A Case Report and Review of the Literature - Yuyu Ishimoto; Mamoru Kawakami; Elizabeth Curtis; Cyrus Cooper; Nami Moriguchi; Yukihiro Nakagawa (Case Reports in Orthopedics)
Ligamentum flavum hematoma (LFH) is a rare cause of spinal nerve compression. This condition remains challenging to diagnose using MRI due to the changing intensity of the hematoma on imaging. The aim of this study was to describe the patient with LFH who had a succession of MRI scans carried out. We report on a 71-year-old woman with a mass at L4/5 and decompression surgery was performed for her left leg symptom. She had MRI carried out in a previous hospital and also had MRI again in our hospital. In a 2nd MRI of the same area, after a 2-week interval, a newly isointense mass was present within the anterior part of the previously identified lesion on T1-weighted image and the hyperintense area in the lesion was a little extended on T2-weighted imaging. Her symptoms were resolved immediately after decompression surgery. Following a review of previous cases, we suggest that consecutive MRI scanning may support the diagnostic process for LFH.